Stabilization of the morphotropic phase boundary in (1 − x)Bi0.5Na0.5TiO3–xBaTiO3 ceramics through two alternative synthesis pathways - Prado, A.; Ramajo, L.; Camargo, J.; del Campo, Adolfo; Öchsner, Paul-Erich; Rubio-Marcos, F.; Castro, M. (Journal of Materials Science: Materials in Electronics, 2019)
In this work, we report the influence of synthesis conditions on the (1 − x)Na0.5Bi0.5TiO3–xBaTiO3 (BNT–BT) system, obtained by the conventional solid-state reaction method with a mechanochemical activation step through two alternative synthesis routes on piezoelectric properties. Samples were characterized by X-ray diffraction (XRD), Raman microspectroscopy and scanning electron microscopy (SEM). It was confirmed that the stabilization of a morphotropic phase boundary (MPB) meaningfully improved the piezoelectric activity. Here, we report that the stabilization of the morphotropic phase boundary (MPB) region in the BNT–BT ceramic systems depended on the selected synthesis pathway. Indeed, samples prepared by the direct mechanochemical activation of all mixed BNT–BT reactants showed a correlation between dielectric and ferroelectric properties and a clear sequence in the permittivity values.
CRIS-Team Scopus Importer:2019-10-25

Synthesis and characterization of Bi0.5Na0.5TiO3-BaTiO3-K0.5Na0.5NbO3 ceramics for energy storage applications - Prado, A.; Camargo, J.; Öchsner, Paul-Erich; Ramajo, L.; Castro, M. (Journal of Electroceramics, 2020)
Structural, microstructural, dielectric, ferroelectric and piezoelectric properties of the (0.95-x)Bi0.5Na0.5TiO3–0.05BaTiO3-xK0.5Na0.5NbO3 (BNT-BT-KNN) lead-free ceramics with 0.0 ≤ x ≤ 0.06 were studied. Samples were synthesized through the mechanochemically activated solid-state method and structurally characterized by X-ray diffraction (XRD) and Raman-spectroscopic studies, whereas the microstructure of all samples was analyzed by Field Emission Scanning Electron Microscopy (FE-SEM). When KNN concentration and temperature were increased, the transition from a ferroelectric to relaxor state was detected by ferroelectric-loop measurements. Furthermore, the high-energy storage efficiency values at room temperature obtained for samples with x ≥ 0.04 confirm the suitability of these ceramics for energy storage applications.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Energy storage materials; Ferroelectricity; Ferroelectrics; Solid-state reaction

Temperature dependent fracture toughness of KNN-based lead-free piezoelectric ceramics - Li, Yingwei; Liu, Yixuan; Öchsner, Paul-Erich; Isaia, Daniel; Zhang, Yichi; Wang, Ke; Webber, Kyle Grant; Li, Jing Feng; Rödel, Jürgen (Acta Materialia, 2019)
The fracture toughness of unpoled and electrically poled lead-free KNN-based piezoelectric ceramics with the composition of 0.92KNN-0.02Bi0.5Li0.5TiO3-0.06BaZrO3 was investigated. Results reveal that at room temperature, the intrinsic fracture toughness (KI0) of the unpoled samples, evaluated by the near-tip crack opening displacement (COD) technique, is the lowest with a value of 0.70 MPa⋅m0.5; the long (through-thickness) crack fracture toughness (KIvnb), obtained by the single edge V-notch beam (SEVNB) technique, is the highest, with a value of 0.95 MPa⋅m0.5; intermediate short surface crack fracture toughness (KIsc) of 0.86 MPa⋅m0.5 was determined by the surface crack in flexure (SCF) technique. These results were rationalized by the toughening behavior of the material combined with the crack geometry-dependent stress intensity evolution during crack propagation. With increasing temperature, KIvnb and KIsc decrease, and become nearly identical at 350 °C, suggesting an absence of toughening. For electrically poled samples, their room temperature fracture toughness was characterized by both SCF and SEVNB techniques, with values of 0.88 MPa⋅m0.5 and 0.99 MPa⋅m0.5, respectively, slightly larger than the values measured for unpoled samples. Nonlinear electric field-strain and stress-strain analysis of the material was also employed during electric field loading, mechanical compression and four-point bending in order to quantify crack tip shielding by domain switching and the actual stress at the point of instable crack propagation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Domain switching; Fracture toughness; Lead-free piezoceramics; Potassium-sodium niobate; Toughening